Optimizing Asset Recovery in Recovering State Losses from Money Laundering Crimes through the Deferred Prosecution Agreement (DPA) - Nurul Annisa; Awaluddin Awaluddin; Syachdin Syachdin (Universitas Islam Sultan Agung, 2026)
This study analyzes the optimization of asset recovery and the restitution of state losses in money laundering crimes by strengthening the authority of public prosecutors and implementing the Deferred Prosecution Agreement (DPA) procedure within the framework of national criminal law reform. The main problem lies in the low asset recovery ratio compared to the magnitude of state losses due to corruption and money laundering, indicating that law enforcement is still oriented towards punishing perpetrators, rather than asset recovery. The enactment of Law No. 1 of 2023 concerning the Criminal Code and Law No. 20 of 2025 concerning Criminal Procedure Law opens up space for strengthening prosecutorial discretion based on restorative justice. This study uses normative legal methods with a statutory and conceptual approach, and is supported by primary data through interviews with law enforcement officials. The results show that the dominus litis principle provides strategic bargaining power to public prosecutors to direct case resolution towards the recovery of state losses. The DPA procedure can be an effective instrument in accelerating asset recovery, especially in cases involving corporations and cross-jurisdictional transactions, including digital assets and cryptocurrencies. However, the implementation of the DPA must be accompanied by judicial oversight, clear operational standards, and proportionality testing to maintain a balance between effective law enforcement and human rights protection. Therefore, optimizing the authority of public prosecutors through the DPA has the potential to significantly increase the effectiveness of asset recovery in Indonesia's modern economic criminal justice system.